(untitled) (Research, Society and Development, 2022)
Land tenure regularization aims to legalize the property of residents of urban areas irregularly occupied for housing purposes and consequently provide security, improve the urban environment and the population’s quality of life. This research aims to study how the process of legalization of occupations in Goiânia, contributed as an instrument of social inclusion of low-income people. In order to answer: does urban land regularization contribute as an instrument of inclusion for the low-income population to have access to housing? In this context, through an exploratory bibliographic research, which had in documents its main source for collecting information, for the case study carried out in the neighborhoods Quebra Caixote, Vila Lo-bó, St. University, Vila Romana, have been regulated or in the process of being legalized. Thus, the procedure implemented by the city hall of Goiânia, through the title and ownership of housing, in the neighborhoods, ended up ending, for these residents, the dignity of the urban space, contributing as an instrument of social inclusion, meeting the demand for housing and legal security. of the property.